Expanding needle concept for better extraction of body hair grafts - Arvind Poswal (Wolters Kluwer Medknow Publications, 2013)
In traditional follicular unit extraction technique, 0.8-1.4 mm punch is used to cut the dermis to the level of attachment of erector pili muscle, so that the intact follicular unit grafts can be extracted. However, the larger extraction sites and higher hair root transection rates are some difficulties encountered while using the punch to extract body hair grafts. To overcome these difficulties, expanding needle concept has been devised. It approaches the extraction process by customizing the extraction wound to the architecture of the follicular unit and by performing most of the dissection of the dermal attachments to the donor follicular unit under direct magnified vision.